The effectiveness of a combination of probiotics and natural wheat and sesame based prebiotics in enhancing the growth performance of giant freshwater prawns (Macrobrachium rosenbergii) - Maharani Khairunnisa; Eko Rini Farastuti; Ananingtyas S Darmarini; Yani Aryati (Universitas Djuanda, 2026)
The main challenge in farming M. rosenbergii is its relatively slow growth rate, which directly affects productivity and profitability. This research evaluates the effectiveness of probiotic and prebiotic combinations based on wheat and sesame (synbiotics) on the growth performance of giant prawns. This research used a Completely Randomized Design (CRD) with four treatments: Control (P1), Probiotic (P2), Wheat-based Synbiotic (P3), and Sesame-based Synbiotic (P4), each replicated three times. Observed parameters included growth performance, feed conversion ratio (FCR), survival rate, and intestinal histology. Treatment P3 provided the best result with an average weight gain of 4.03 ± 1.85 g, a specific growth rate (SGR) of 0.61 ± 0.23% per day, a length gain of 1.82 ± 0.45 cm, and a specific growth rate of length (SLGR) of 0.27 ± 0.06% per day. The lowest Feed Conversion Ratio (FCR) was found in P3, at 2.66 ± 0.53 g, indicating the best feed efficiency and more uniform and longer intestinal microvilli. The survival rate in P3 reached 93.33 ± 11.55%. Treatment P3 improved growth, feed efficiency, and intestinal health in giant prawns. Additional studies are suggested to investigate the molecular mechanisms by which synbiotics affect digestive and immune-related genes.